An In-depth Qualitative Analysis of Situated Learning Instruction in Situation Awareness for Military English Course - Hsiu-Yu Yao; Yu-Tang Hung (Script Journal: Journal of Linguistics and English Teaching, 2021)
While situated learning (SL) instruction has been adopted for educational purposes in many fields, an SL environment for military English has not been considered. Situation awareness (SA) is an important theme in the military English course, SL instruction can be a suitable method to enhance cadets’ learning performance in SA operation. This study investigated the SA concept formation and operation as the effects of conducting SL instruction. A film acted as an authentic military context, which sixteen cadets in Taiwan, R.O.C. accessed to perform SA. On the basis of Blooms’ six cognition levels, the researchers gave an in-depth qualitative analysis over their learning performance of SA. The research tools include worksheets, English role-plays, and concept maps. Worksheets were designed to observe their SA concept formation in four film situations during Endsley’s three steps of SA: perception, comprehension, and projection. The researchers used English role plays to judge whether they actively operated SA and concept maps to see if they formed new SA concepts.